Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) Terhadap Dosis LimbaCair Pabrik Kelapa Sawit dan Tipe Pemotongan Umbi - Andi Setiawan; Rosita Sipayung; Toga Simanungkalit (Universitas Sumatera Utara, 2015)
The research aimed to study about the response of growth and yield of shallot on palm oil milleffluent (POME) and type of bulb fission. The research has been conducted on land of AgriculturalFaculty USU (± 25masl) from April to Juny 2014, using a factorial randomized block design withtwo factors which are dosage of effluent (0; 1; 2; 3 l/plot) and the second factors were type offission (no fission, fissioned 1/3 part, fissioned into 2 part). The Parameters observed were plantheight, leaves number per clump, tillers number per clump, clove number, wet weight of bulb perplant, wet weight of bulb per plot, dry weight of bulb per plant and dry weight of bulb per plot. Theresults showed bulb fission treatment significantly increased for all parameters. Giving palm oil milleffluent significantly increased clove number and interaction of fission bulb treatment and givingpalm oil mill effluent non significantly increased for all parameters.Keywords:shallot, POME, fission